Visual augmentation of source code editors: A systematic mapping study. (December 2018) - Sulír, Matúš; Bačíková, Michaela; Chodarev, Sergej; Porubän, Jaroslav
Highlights: Source code augmentation is visualization located directly in plain-text source code. We performed a systematic mapping study, resulting in a list of 103 articles. The surveyed tools were categorized in a taxonomy with 7 dimensions. Abstract: Source code written in textual programming languages is typically edited in integrated development environments (IDEs) or specialized code editors. These tools often display various visual items, such as icons, color highlights or more advanced graphical overlays directly in the main editable source code view. We call such visualizations source code editor augmentation. In this paper, we present a first systematic mapping study of source code editor augmentation tools and approaches. We manually reviewed the metadata of 5553 articles published during the last twenty years in two phases – keyword search and references search. The result is a list of 103 relevant articles and a taxonomy of source code editor augmentation tools with seven dimensions, which we used to categorize the resulting list of the surveyed articles. We also provide the definition of the term source code editor augmentation, along with a brief overview of historical development and augmentations available in current industrial IDEs.